Identification and Characterization of the fis Operon in Enteric Bacteria - Beach, Michael B.; Osuna, Robert (Journal of bacteriology, 1998)
The small DNA binding protein Fis is involved in several different biological processes in Escherichia coli . It has been shown to stimulate DNA inversion reactions mediated by the Hin family of recombinases, stimulate integration and excision of phage λ genome, regulate the transcription of several different genes including those of stable RNA operons, and regulate the initiation of DNA replication at oriC. fis has also been isolated from Salmonella typhimurium , and the genomic sequence of Haemophilus influenzae reveals its presence in this bacteria. This work extends the characterization of fis to other organisms. Very similar fis operon structures were identified in the enteric bacteria Klebsiella pneumoniae , Serratia marcescens , Erwinia carotovora , and Proteus vulgaris but not in several nonenteric bacteria. We found that the deduced amino acid sequences for Fis are 100% identical in K. pneumoniae , S. marcescens , E. coli , and S. typhimurium and 96 to 98% identical when E. carotovora and P. vulgaris Fis are considered. The deduced amino acid sequence for H. influenzae Fis is about 80% identical and 90% similar to Fis in enteric bacteria. However, in spite of these similarities, the E. carotovora , P. vulgaris , and H. influenzae Fis proteins are not functionally identical. An open reading frame (ORF1) preceding fis in E. coli is also found in all these bacteria, and their deduced amino acid sequences are also very similar. The sequence preceding ORF1 in the enteric bacteria showed a very strong similarity to the E. coli fis P region from −53 to +27 and the region around −116 containing an ihf binding site. Both β-galactosidase assays and primer extension assays showed that these regions function as promoters in vivo and are subject to growth phase-dependent regulation. However, their promoter strengths vary, as do their responses to Fis autoregulation and integration host factor stimulation.